79P Nivolumab treatment beyond progression disease in advanced non-small cell lung cancer. (15th December 2019) - Enomoto, T; Tamiya, A; Matsumoto, K; Adachi, Y; Azuma, K; Inagaki, Y; Kouno, S; Taniguchi, Y; Saijo, N; Okishio, K; Atagi, S
Abstract: Background: Nivolumab is one of immune checkpoint inhibitors, which is reported to have efficacy in previously treated patients with advanced non-small cell lung cancer (NSCLC) in checkmate 017 / 057 / 078. It is suggested nivolumab treatment beyond progression disease (PD) may be associated with improved survival in patients with melanoma and renal cell carcinoma. However, the efficacy of beyond PD in patients with NSCLC is still unclear. Methods: To evaluate the efficacy of beyond PD about nivolumab, we retrospectively reviewed the continuous patients with advanced NSCLC, who received nivolumab as 2nd line treatment in our institution between February 2016 and February 2019. The patients were eligible if they had been diagnosed PD using RECIST v1.1 by 28 February 2019. Baseline characteristics, overall response rate (ORR), disease control rate (DCR), progression free survival (PFS), overall survival (OS), the period between RECIST v1.1 PD and clinical PD, post-PD OS, and safety were evaluated on 26 July 2019. Results: Of the 144 advancer NSCLC patients treated with 2nd line nivolumab, 95 patients were eligible. Post-PD OS was 12.2 months (95% confidence interval [CI]: 5.8–26.6) in 28 patients continuing nivolumab beyond PD, 9.3 months (95% CI: 6.4–13.8) in 46 patients switching to other anti-cancer therapy, and 0.7 months (95% CI: 0.4–1.7) in 21 patients receiving no further therapy. The median period between RECIST v1.1 PD and clinical PD was 3.8 months (95% CI: 2.8–6.6) in 28 patients continuing nivolumab beyond PD. During nivolumab beyond PD, one patient died due to acute liver involvement and interstitial lung disease, one patient stopped to receive nivolumab due to grade 3 diarrhea, and one patient stopped to receive nivolumab due to grade 2 interstitial lung disease. Conclusion: Post-PD OS trended to be longer in patients continuing nivolumab beyond PD than in patients switching to other anti-cancer therapy. Within the limitations of this retrospective analysis, this study suggests nivolumab treatment beyond PD may have efficacy and safety in patients with advanced NSCLC. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.